A dataset listing the parents of the G19 GIFT growth line families - Mahmuddin, Mahirah; Hamilton, Matthew (2025)
This dataset recorded 60 parents of the G19 GIFT growth line families spawned from January to April 2024. Data contains the date of egg collection, count at collection and date of fry collection.